Pregnancy-related cardiovascular conditions and outcomes in a United States Medicaid population. Issue 19 (13th April 2022) - Marschner, Simone; von Huben, Amy; Zaman, Sarah; Reynolds, Harmony R; Lee, Vincent; Choudhary, Preeti; Mehta, Laxmi S; Chow, Clara K
Abstract : Objective: This study aims to examine the incidence of pregnancy-related cardiometabolic conditions and severe cardiovascular outcomes, and their relationship in US Medicaid-funded women. Methods: Medicaid is a government-sponsored health insurance programme for low-income families in the USA. We report the incidence of pregnancy-related cardiometabolic conditions (hypertensive disorders and diabetes in, or complicated by, pregnancy) and severe cardiovascular outcomes (myocardial infarction, stroke, acute heart failure, cardiomyopathy, cardiac arrest, ventricular fibrillation, ventricular tachycardia, aortic dissection/aneurysm and peripheral vascular disease) among Medicaid-funded women with a birth (International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) diagnosis code O80 or O82) over the period January 2015–June 2019, from the states of Georgia, Ohio and Indiana. In this cross-sectional cohort, we examined the relationship between pregnancy-related cardiometabolic conditions and severe cardiovascular outcomes from pregnancy through to 60 days after birth using multivariable models. Results: Among 74 510 women, mean age 26.4 years (SD 5.5), the incidence per 1000 births of pregnancy-related cardiometabolic conditions was 224.3 (95% CI 221.3 to 227.3). The incidence per 1000 births of severe cardiovascular conditions was 10.8 (95% CI 10.1 to 11.6). Women with pregnancy-related cardiometabolic conditions were at greater risk of having a severe cardiovascular condition with an age-adjusted OR of 3.1 (95% CI 2.7 to 3.5). Conclusion: This US cohort of Medicaid-funded women have a high incidence of severe cardiovascular conditions during pregnancy. Cardiometabolic conditions of pregnancy conferred threefold higher odds of severe cardiovascular outcomes.